Developmental Psychology In the Arabic Language Learning and Teaching Process/ Psikologi Perkembangan Dalam Proses Belajar Mengajar Bahasa Arab - Nuzula, Firdausi; Mufidah, Nuril (Bumi Lingua Edu Center, 2024)
This article discusses the importance of developmental psychology in learning and teaching the Arabic language. Data were obtained from a literature study in the form of journal article documents and reference books related to developmental psychology and Arabic language learning. The results of the study showed that developmental psychology provides insights into how individuals develop cognitively, socially, and emotionally at various stages of their lives. This understanding is crucial for teachers in designing and implementing effective teaching strategies that cater to the needs of students. The article highlights how teaching strategies tailored to students' developmental stages can enhance motivation and learning outcomes. Additionally, the article identifies the challenges teachers face in applying the principles of developmental psychology, such as individual differences among students, limited resources, and inadequate training. Teachers can create a more inclusive and effective learning environment by addressing these challenges through continuous support and training. Implementing developmental psychology in Arabic language teaching is expected to help students reach their full potential and improve the overall quality of education.